Physical Exercise Program for Elderly Subjects in the “Club Nueva Vida”, in Tunja City - Carolina Sandoval Cuellar; Magda Liliana Camargo; Diana Marcela González Ochoa; Yenny Patricia Vélez Ruiz (Revista Ciencias de la Salud, 2007)
A descriptive, case series intervention study wasperformed to identify changes in physical qualities,aerobic power, flexibility, strength and bodycomposition amongst 20 elderly subjects belongingto the “Club Nueva Vida” in Tunja City,during the second period of 2005. A PRE andPOST assessment of their physical qualitieswas applied after a 16 week physical exerciseprogram.Results showed an increase in the average ofthe static muscle streneth from 0.27 to 0.30Newtons. Standard deviation diminished in 0.1.The dynamic strength measure by the push uptest improved in 10% a 35% improved in 10%a 35% improved their.Cardiovascular capability until to high levelsof 80% there were not significant changes inthe body weight between measures taken beforeand after the program application.The results obtained with the sit and reach testdid not show statistically significant differences.Hower in other flexibility tests the results changedfrom bad ranges to middle and good ones.The enrolled population was stable duringthe development of the exercise program.This study concludes that elderly adults acquirechanges in their physical quality featuresafter exercise intervention. Physical exerciseprograms in elderly adults must involve strengthactivities for upper limbs, trunk and aerobicpower activities. The “Beliefs Health Model” is aadherence to reach compliance and maintenancein physical exercise.